-3-3n=-n+3

Simple and best practice solution for -3-3n=-n+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3-3n=-n+3 equation:


-3-3n=-n+3

We simplify the equation to the form, which is simple to understand
-3-3n=-n+3

We move all terms containing n to the left and all other terms to the right.
-3n+1n=+3+3

We simplify left and right side of the equation.
-2n=+6

We divide both sides of the equation by -2 to get n.
n=-3

See similar equations:

| ln(x+-3)+ln(x+2)=ln(x+-7) | | 1/5x+5h-1/5x | | -4m-13=5-m | | 6k+2=16+4k | | x+2=-68 | | 26=2x-14 | | (9i+11i)/10i | | Y-x=4x^2-8 | | -3-8x+7x=-3+5x | | 14=8z+6 | | log(7)16807=y | | 12m-71=25 | | 8p+4p+6=3p+7p | | 2x-x-3=5 | | 5b(b+4c)= | | x^2+0x+14=0 | | 247=-v+5(6v+3) | | 4y-9=27 | | 6(-1-6x)=246 | | 21/3=m/42 | | -343=-8(7-7a) | | 5(x-1)=5(4x-3) | | s^13t^8/s^2t | | 0=24x^2+28x-24 | | 3n+1=4n-2 | | -5(1-5x)+5x(-8x-2)=-4x-8x | | 24/15=20 | | 36=(6x+1)/(x-6) | | X^2-5x-36=4x | | X^3=-2x^2+8x | | (X+5)/4=-7 | | 16=(6x+1)/(x-1) |

Equations solver categories